Solve (x + 2)y"-(2x + 5)y'
+ 2y = (x + 1)ex
Solution
One of the solutions of homogeneous equation (x + 2)y0"-(2x + 5)y0'+ 2y0 = 0 let’s find in the form y0(x) = erx. Substitution into equation gives
(x + 2)r2-(2x + 5)r+ 2= 0 => x(r2-2r)+(2r2-5r+2) = 0 => from first brackets equal to zero r=0, r=2 and from second r = 1/2, r = 2 => r = 2
So y01(x) = e2x.
Once we have this first solution we will then assume that a second solution of homogeneous equation will have the form
y(x) = y01(x)u(x)
Plugging this into the homogeneous equation gives
(x+2)u’’+(2x+3)u’ = 0
New function w(x) = u’(x) => (x+2)w’ = -(2x+3)w => dw/w = -(2x+3)dx/(x+2) => ln|w| = - 2x+ln|x+2| + C1 => w = C1 (x+2)e-2x => u(x) = C2+∫w(x)dx = C2+ C1∫(x+2)e-2x dx = C2 - C1 (x/2+5/4) e-2x => y0(x) = y01(x)u(x) = C2 e2x - C1 (x/2+5/4)
Partial solution of initial nonhomogeneous equation let’s find in the form y1(x) = Aex
Plugging this into the nonhomogeneous equation gives
A[(x+2)-(2x-5)+2] = x+1 => A(-x-1) = x+1 = > A = -1 => y1(x) = - ex
Therefore solution of initial equation is
y(x) = y0(x) + y1(x) = C2 e2x - C1 (x/2+5/4) - ex
Comments
Leave a comment